Knowledge and Understanding of Corporate Social Responsibility - KOT, Sebastian (Journal of Advanced Research in Law and Economics; Vol 5 No 2 (2014): JARLE Volume V, Issue 2(10), Winter 2014, 2017)
Corporate Social Responsibility is a concept which has become dominant in business reporting. Many corporations have a policy concerning CSR and produce a report annually detailing its activity. And of course each of us claims to be able to recognize corporate activity which is socially responsible and activity which is not socially responsible. It is not a new concept, but unfortunately has been defined in so many ways and it is often misinterpreted. The aim of the article is to analyze level of knowledge and understanding of the theoretical basis of corporate social responsibility. The author presents the concept of corporate social responsibility and puts his attention on the lack of agreed definition and areas which CRS influences. He also indicates main benefits of corporate social responsibility.